2016
DOI: 10.1016/j.biomaterials.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Polymer brain-nanotherapeutics for multipronged inhibition of microglial α-synuclein aggregation, activation, and neurotoxicity

Abstract: Neuroinflammation, a common neuropathologic feature of neurodegenerative disorders including Parkinson disease (PD), is frequently exacerbated by microglial activation. The extracellular protein α-synuclein (ASYN), whose aggregation is characteristic of PD, remains a key therapeutic target, but the control of synuclein trafficking and aggregation within microglia has been challenging. First, we established that microglial internalization of monomeric ASYN was mediated by scavenger receptors (SR), CD36 and SRA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 77 publications
1
17
0
Order By: Relevance
“…In vivo studies in a PD mouse model showed that the AM NPs can reduce ASYN deposition in the CNS as well as reduce microglial activation and recruitment, which were achieved by the combinatorial effect of the scavenger receptor-targeting AM shell and anti-inflammatory ferulic acid polymer components. 189 This result highlights the use of NP formulations as a unique drug delivery platform, which not only supports but also strengthens the activity of the bioactive agent and enables targeted delivery.…”
Section: Targeting Microglia Using Nanotherapeuticsmentioning
confidence: 68%
See 1 more Smart Citation
“…In vivo studies in a PD mouse model showed that the AM NPs can reduce ASYN deposition in the CNS as well as reduce microglial activation and recruitment, which were achieved by the combinatorial effect of the scavenger receptor-targeting AM shell and anti-inflammatory ferulic acid polymer components. 189 This result highlights the use of NP formulations as a unique drug delivery platform, which not only supports but also strengthens the activity of the bioactive agent and enables targeted delivery.…”
Section: Targeting Microglia Using Nanotherapeuticsmentioning
confidence: 68%
“…One example is a scavenger receptor-targeting amphiphilic macromolecule-based NP (AM NP) design, carrying ferulic acid-derived polymer as a therapeutic agent. 189 These AM NPs were designed to have strong affinity to scavenger receptors, specifically CD36 and SR-A1 on microglia, and can weaken the receptor binding of ASYN, thus reducing ASYN aggregation-induced microglial activation. In vivo studies in a PD mouse model showed that the AM NPs can reduce ASYN deposition in the CNS as well as reduce microglial activation and recruitment, which were achieved by the combinatorial effect of the scavenger receptor-targeting AM shell and anti-inflammatory ferulic acid polymer components.…”
Section: Targeting Microglia Using Nanotherapeuticsmentioning
confidence: 99%
“…An interesting least-component based approach of targeted drug delivery using bioactive polymers, wherein polymers are engineered to have targeting moieties, replacing the need of conjugating additional targeting ligands like antibodies, was developed by Prof Kathryn Uhrich (Gu et al, 2014; Zhang et al, 2015). Her team formulated a library of sugar-based amphiphiles with geometries similar to liposomes, hydrophobic core (to encapsulate drug), and hydrophilic shell, wherein the shell is engineered to have targeting moieties (Gu et al, 2014) and then screened these bioactive polymers for their anti-cancer and anti-Parkinson activities (Bennett et al, 2016; Gu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The inequality of these activation in microglial cells may lead to either neural benefit or damage. The activation of microglial cells in terms of chronicity is believed to be related to neurodegenerative disorders (Alzheimer’s disease [ 10 , 11 , 12 ] and Parkinson’s disease [ 13 , 14 , 15 ]). Hence, the inhibition of microglial activation has been suggested for potential treatment of neurodegenerative diseases [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%